Literature Study: Chemical Content and Benefits of Bidara Leaves (Ziziphus Muritiana) as an Indonesian Herbal - hajeriani (Hayyan Journal, 2024)
Plants with various varieties can be found in various regions in Indonesia. Many varieties of medicinal plants in Indonesia have been used as raw materials for making medicines and several of these plant types have been clinically evaluated for their phytochemical composition, efficacy and safety of use. Bidara leaves, scientifically known as Zizhipus mauritiana L., are often used in Traditional Chinese Medicine to cure a number of diseases, such as urinary problems, digestive disorders, fever, liver complaints, weakness, anemia, obesity, diabetes, bronchitis, skin infections, loss of appetite. eating, pharyngitis, diarrhea, cancer, and insomnia. The reference literature obtained from the search results is then studied and examined to determine research findings, then described using the data or samples collected as is. Based on research and literature studies, bidara leaves have various significant health benefits, especially because of their rich chemical compound content. The flavonoid, tannin, terpenoid, steroid, alkaloid, triterpenoid and saponin compounds in bidara leaves have been proven to have anti-microbial, anti-depressant, anti-inflammatory, anti-oxidant and anti-cancer activity. Furthermore, bidara leaves can also protect body cells such as the kidneys and brain from oxidative stress, which is one of the main risk factors for cancer. Therefore, bidara leaves can be a safe and natural alternative treatment for various diseases and health conditions.